Cancer Susceptibility Candidate 9 (CASC9) Promotes Colorectal Cancer Carcinogenesis via mTOR-Dependent Autophagy and Epithelial–Mesenchymal Transition Pathways - Islam Khan, Md Zahirul; Law, Helen Ka Wai (Frontiers in Molecular Biosciences, 2021)
Background: Colorectal cancer (CRC) is the third most common cancer worldwide. Many recent studies have demonstrated that different long non-coding RNAs (lncRNAs) are involved in the initiation, advancement, and metastasis of many cancer including CRC. Cancer susceptibility candidate 9 (CASC9) is an lncRNA that has been reported in many cancers but its role in CRC is poorly understood. In this study, we aimed to examine the expression of CASC9 in CRC cell lines and to determine the mechanism of action of CASC9 in CRC carcinogenesis. Methods: The expression of CASC9 in CRC tissues was compared with normal samples from publicly available datasets in The Cancer Genome Atlas (TCGA) and Encyclopedia of RNA Interactomes (ENCORI). CASC9 expression was further verified in 4 CRC cell lines (DLD1, HT-29, SW480 and HCT-116) and normal colorectal cell line (CCD-112CoN) by real time quantitative polymerase chain reaction. After gene silencing in HCT-116 and SW480, Cell Counting Kit-8 assay, clonogenic assay, and wound healing assay were performed to evaluate cell proliferation, viability, and migration index of cells. Western blotting was used to explore the key pathways involved. Results: CASC9 was significantly upregulated as analysed from both public datasets TCGA and ENCORI where its overexpression was associated with poor survival of CRC patients. Similarly, CASC9 was significantly overexpressed in the CRC cell lines compared with normal cells studied. The silencing of CASC9 in HCT-116 and SW480 attenuated cell proliferation and migration significantly. Furthermore, pathways investigations showed that silencing of CASC9 significantly induced autophagy, promoted AMP-activated protein kinase (AMPK) phosphorylation, inhibited mTOR and AKT signalling pathways and altered epithelial-mesenchymal transition (EMT) marker protein expression. Conclusion: We demonstrated that silencing of CASC9 contribute to the reduced CRC cell proliferation and migration by regulating autophagy and AKT/mTOR/ EMT signalling. Therefore, CASC9 plays an important role in carcinogenesis and its expression may act as a prognostic biomarker and a potential therapeutic target of CRC management.